HUBUNGAN ZAT GIZI MAKRO, AKTIVITAS FISIK DENGAN STATUS GIZI ANAK SDN 46 GEDONG TATAAN TAHUN 2021 - Dewi Fortuna Saraswati; Ramadhana Komala; Amali Rica Pratiwi; Desti Ambar Wati (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2022)
Background: Nutritional problems in school-age children are overnutrition and undernutrition, factors that affect nutritional status include macronutrient intake and physical activity. If the intake of macronutrients that enter the body is excessive and does not do physical activity, there will be an increase in body weight. The prevalence of BMI/U nutritional status in children aged 5-12 years in Lampung province is 4.76% very thin, 4.75% thin, and obese 8.52%. Research Objectives: The purpose of this study was to determine the relationship between macronutrient intake and physical activity with nutritional status in 46 Gedong Tataan elementary school children in 2021. Methods: Research design using analytic with cross sectional approach. Analysis of the data used is the Spearman Correlation Test and the Pearson Correlation Test. The sample in this study amounted to 70 people. Research Result: Research shows that there is a relationship between intake of energy, protein, fat, and carbohydrates with nutritional status in elementary school children with p = 0.000. There is no relationship between physical activity and nutritional status in elementary school children with p = 0.513. Conclusion: The conclusion of this study is that there is a significant relationship between intake of energy, protein, fat, and carbohydrates with the nutritional status of school children. There is no relationship between physical activity and nutritional status of school children.